Human–object interaction, connectedness with nature, and life satisfaction: a cross-sectional study - Kamide, Hiroko; Arai, Tatsuo (Frontiers in Psychology, 2024)
Introduction This study aimed to elucidate the relationship between interactions with everyday objects (e.g., stationery, clothing, and tools) and one’s connectedness with nature, environmentally conscious behavior, and life satisfaction. While previous research has predominantly explored the link between awareness of and behavior toward nature with direct education and experience related to the natural environment, we focused on the origins of the objects that surround us, which are inherently derived from nature. Methods We conducted an online survey with 1,102 Japanese participants, who completed an object–interaction measure assessing the two dimensions of care and learning, and measures of connectedness with nature, pro-environmental behavior, and life satisfaction. Results Interactions with everyday objects involving care and learning were significantly associated with a sense of connectedness with nature, pro-environmental behavior, and life satisfaction. Discussion The study highlights that interactions with everyday artifacts are not isolated experiences but are related to broader awareness of and behavior toward the natural world, and with individual life satisfaction. Hence, environmental awareness and actions can extend beyond direct environmental experiences and encompass daily interactions with objects. Future research could examine how cultural factors shape the relationship between human–object interactions, connection with nature, environmentally conscious behavior, and life satisfaction.